Synthesis and characterization of silver nanoparticles in lamellar lyotropic liquid crystal / Siti Mariah Mohd Yasin - Siti Mariah , Mohd Yasin (2020)
Lamellar lyotropic liquid crystal-silver nanoparticles (LLLC-AgNPs) are synthesized using the in-situ method. The polarizer microscope showed a mosaic-like pattern with fan shape textures. The high resolution transmission electron microscope (HRTEM) confirmed that the AgNPs are spherical in shape with 4 – 12 nm size. Differential scanning calorimetry (DSC) determined the LLLC-AgNPs transition anisotropic phase to the highly ordered isotropic phase at 300 °C, and crystallinity was completed at 350 °C. Thermogravimetric analysis (TGA) verified that the LLLC-AgNPs were completely decomposed at 700 °C. Ultra-violet visible spectroscopy (UV-vis) found the absorption peaks at around 400 nm and proved that the AgNPs is distributed in a polydispersed manner. With the increase in temperature, the polydispersity behavior decreases indicating that the AgNPs' growth is restricted and the nucleation process took part. The absorption and bandwidth decrease after 4 weeks which proves that the AgNPs is distributed in a monodispersed manner. The granularity and dispersity of AgNPs were further confirmed by photoluminescence (PL). By varying pHs, surface enhance Raman spectroscopy (SERS) demonstrated the high signal of 4-ABT at pH = 5 – 12. The electrical potential achieved maximum, +70.7 mV at pH = 5 – 6, and all pH ranges still exceed the minimum stability within 2 months, which proves the super stability of AgNPs dispersed in the LLLC domain. The vector network analyzer (VNA) verified that the LLLC is a lossy dielectric and radiates higher magnetic energy, while, the LLLC-AgNPs are exhibited as storing dielectric material and radiating lower of magnetic energy.